INOVASI MEDIA PEMBELAJARAN INTERAKTIF UNTUK MATEMATIKA DASAR BANGUN DATAR - Restu Narendrastomo; Khairul Ikhsan; Ardya Zahira Ardhana (PT. Hasba Edukasi Mandiri, 2025)
The use of technology in learning continues to grow and leads to the development of various new learning media. In this study, an interactive multimedia-based learning application was developed for teaching plane shapes. The development process used the Luther Sutopo method, which includes six stages: concept, design, material collecting, assembly, testing, and distribution. This application is designed to help students learn plane shapes in a more engaging way through visual elements and interactive features, rather than relying only on traditional reading methods. It provides learning materials, practice questions, quizzes, and a simple game to increase students’ interest in learning. Based on black box testing, all features in the application worked properly without any errors. This learning media is expected to make the learning process more enjoyable and help students understand plane shapes more easily.